Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/emmm.201302567
|View full text |Cite
|
Sign up to set email alerts
|

Pathological impact of SMN 2 mis‐splicing in adult SMA mice

Abstract: Loss-of-function mutations in SMN1 cause spinal muscular atrophy (SMA), a leading genetic cause of infant mortality. The related SMN2 gene expresses suboptimal levels of functional SMN protein, due to a splicing defect. Many SMA patients reach adulthood, and there is also adult-onset (type IV) SMA. There is currently no animal model for adult-onset SMA, and the tissue-specific pathogenesis of post-developmental SMN deficiency remains elusive. Here, we use an antisense oligonucleotide (ASO) to exacerbate SMN2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 69 publications
1
28
0
Order By: Relevance
“…On the other hand, in several studies, including our own, selective depletion of SMN in motor neurons induces NMJ defects, and restoration of SMN rescues them, indicating a cell-autonomous mechanism (Park et al 2010;Gogliotti et al 2012;Lee et al 2012;Martinez et al 2012;Sahashi et al 2012Sahashi et al , 2013. This apparent discrepancy may be due to the extremely low SMN levels in motor neurons in these studies.…”
Section: Discussionmentioning
confidence: 57%
“…On the other hand, in several studies, including our own, selective depletion of SMN in motor neurons induces NMJ defects, and restoration of SMN rescues them, indicating a cell-autonomous mechanism (Park et al 2010;Gogliotti et al 2012;Lee et al 2012;Martinez et al 2012;Sahashi et al 2012Sahashi et al , 2013. This apparent discrepancy may be due to the extremely low SMN levels in motor neurons in these studies.…”
Section: Discussionmentioning
confidence: 57%
“…Given that (1) few genotype-driven changes were present in a model of severe SMA and (2) significant early post-natal expression changes in the mouse spinal cord would likely confound any changes mediated by ASO therapy, we decided to analyze gene-expression changes in a more recently characterized induced model of SMA [12,13]. To evaluate the time course of transcriptional changes induced by skipping SMN2 exon 7 beyond background levels of exon 7 exclusion, 15-week-old mice with mild SMA (Smn -/-; SMN2 +/+ ) [7] were given a single ICV bolus injection of 50 μg exon 7 skip ASO 20-37 or a control ASO, and central nervous system tissue (spinal cord and brain) was collected 10, 20 or 30 days after treatment (Table 1).…”
Section: Induction Of Sma In Adult Mice Causes a Delayed And Coordinamentioning
confidence: 99%
“…Therefore, an induced model of SMA was developed by administering adult mice with mild SMA an ASO, designated ASO 20-37, that targets a purine-rich exon splicing enhancer region in the middle of exon 7 and promotes skipping of SMN2 exon 7 beyond background levels of exon 7 exclusion [12,13]. We recently described the phenotypic and histopathologic effects of induced SMN depletion and repletion with and , respectively, delivered by intracerebroventricular (ICV) injection in neonatal [12] and adult [13] mice with SMA. The consequences of SMN2 mis-splicing were progressive and dose dependent.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to understand the link between RNA processing changes and gene-level changes in SMA and to further investigate the Cdkn1a activation, we characterized spinal cord transcriptome changes by RNAseq at high depth in an ASO-mediated inducible mouse model of type I SMA, which bypasses confounding developmental changes (6,7). Expanding on the aforementioned studies showing snRNP assembly defects and splicing changes, we found that thousands of introns in functionally diverse genes were retained in a manner correlating with splice site strength, such that introns with weaker splicing signals were more sensitive to SMN depletion.…”
Section: Significancementioning
confidence: 99%
“…Importantly, SMN2 copy number varies across individuals and is a modifier of disease severity, with a higher copy number leading to reduced severity. We previously characterized the function of an antisense oligonucleotide (ASO) that binds and blocks an exonic splicing silencer in exon 7 of SMN2 pre-mRNA, enhancing the inclusion of exon 7 and the production of full-length protein when delivered to the cerebrospinal fluid in an inducible mouse model of type I SMA (6,7). We found that early treatment with an ASO that promoted SMN2 exon 7 inclusion prevented and reversed the gene expression changes that occurred on disease induction (6).…”
mentioning
confidence: 99%